A prospective trial of intraoperative tissue oxygenation measurement and its association with anastomotic leak rate after Ivor Lewis esophagectomy - Adusumilli, Prasad S. (J Thorac Dis, 2020)
BACKGROUND: Anastomotic leak following Ivor Lewis esophagectomy is associated with increased morbidity/mortality and decreased survival. Tissue oxygenation at the anastomotic site may influence anastomotic leak. Methods for establishing tissue oxygenation at the anastomotic site are lacking. METHODS: Over a 2-year study period, 185 Ivor Lewis esophagectomies were performed. Study participants underwent measurement of gastric conduit tissue oxygenation at the planned anastomotic site using the wireless pulse oximetry device. Associations between anastomotic leaks or strictures and tissue oxygenation levels were analyzed using Wilcoxon rank sum test or Fisher’s exact test. RESULTS: Among study participants (n=114), median gastric conduit tissue oxygenation level was 92% (range, 62–100%). There were 8 (7.0%) anastomotic leaks and 3 (2.6%) strictures. Analysis of tissue oxygenation as a continuous variable showed no difference in median tissue oxygenation in patients with and without leaks (98% and 92%; P=0.2) and stricture formation (89% and 92%; P=0.6). Analysis of tissue oxygenation as a dichotomous variable found no difference in anastomotic leak rates [7.5% (n=93) in >80% vs. 0% (n=20) in ≤80%; P=0.3]. There were no significant differences in leak rates in concurrent study nonparticipants. CONCLUSIONS: No significant association was observed between intraoperative tissue oxygenation at the anastomotic site and subsequent anastomotic leak or stricture formation among patients undergoing Ivor Lewis esophagectomy.